Factors affecting the debt level among postgraduate students in Islamic Science University of Malaysia (USIM) / Siti Nazifa Yusof - Yusof, Siti Nazifa (2010)
The purpose is to examine the factors that affect debt level among postgraduate student in USIM. A sample of 80 students were volunteered to complete multiple self report instrument for the data collection process. Data was then aggregated and analyzed using Descriptive and Pearson Correlation analysis. Most of the postgraduate students are experienced moderate level whereas others considered as high. The result indicated that marital status is the most factors in affecting the student’s debt level. However, financial aid and credit card usage also had an important role in cumulating the debt level. The study correlates with a discussion of results, limitations and implications for research and practitioners.